2005
DOI: 10.1116/1.2127939
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of nonuniform embossing: The effect of asymmetric neighbor cavities on polymer flow during nanoimprint lithography

Abstract: This paper presents continuum simulations of viscous polymer flow during nanoimprint lithography (NIL) for embossing tools having irregular spacings and sizes. Simulations varied non-uniform embossing tool geometry to distinguish geometric quantities governing cavity filling order, polymer peak deformation, and global mold filling times. A characteristic NIL velocity predicts cavity filling order. In general, small cavities fill more quickly than large cavities, while cavity spacing modulates polymer deformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 19 publications
(32 reference statements)
4
56
0
Order By: Relevance
“…For an array of square pillars r in Equation (1) and w in Equation (2) are given by the following expressions: r ¼ 1 þ 4w(ha À1 ) and w ¼ (ba À1 þ 1) À2 , where a is the pillar width, b the pillar spacing, and h is the pillar height. [22] Our experiments confirm that OTS coated nanopillars prefer the Cassie condition ( Figure 4e) and excel as a superhydrophobic surface with 1638 water contact angle, that is in good agreement with predicted range 157-1628 for a Cassie state assuming pillar width of 100 nm, height of 400 nm and spacing range of 200-300 nm ( Figure 5). According to our experience and the prediction of the Cassie-Wenzel model, to achieve the greatest water contact angle of nanostructured surface with given surface energy, the height/width ratio (ha À1 ) of nanostructure should be larger than 3, and the spacing/width (ba À1 ) ratio should range from 2 to 4.…”
Section: Surface Characterizationsupporting
confidence: 75%
See 1 more Smart Citation
“…For an array of square pillars r in Equation (1) and w in Equation (2) are given by the following expressions: r ¼ 1 þ 4w(ha À1 ) and w ¼ (ba À1 þ 1) À2 , where a is the pillar width, b the pillar spacing, and h is the pillar height. [22] Our experiments confirm that OTS coated nanopillars prefer the Cassie condition ( Figure 4e) and excel as a superhydrophobic surface with 1638 water contact angle, that is in good agreement with predicted range 157-1628 for a Cassie state assuming pillar width of 100 nm, height of 400 nm and spacing range of 200-300 nm ( Figure 5). According to our experience and the prediction of the Cassie-Wenzel model, to achieve the greatest water contact angle of nanostructured surface with given surface energy, the height/width ratio (ha À1 ) of nanostructure should be larger than 3, and the spacing/width (ba À1 ) ratio should range from 2 to 4.…”
Section: Surface Characterizationsupporting
confidence: 75%
“…[21] This contradiction may be caused by the difference of nanopillar height, perhaps, in case of 1 the imprinted nanopillars can be a bit longer due to extremely low viscosity (Table 1). [22] Wetting Properties react with the -OH functionalities forming an organized SAM. The nanopillars coated with OTS are shown in Figure 3d.…”
Section: Surface Characterizationmentioning
confidence: 99%
“…Several recent studies by Rowland et al have investigated the impact of polymer material properties, mold geometry, and process conditions on polymer deformation, and further studied the impact of the polymer deformation mode on the replication time. [90][91][92] They also found that when polymer flows vertically into an open cavity during imprinting, the polymer can deform as a single peak centered in the cavity, or as a dual peak, where each peak remains close to the vertical sidewalls, depending upon the geometry. The ratio of cavity width to film thickness modulates single versus dual peak cavity filling, regardless of the absolute size of the features and the pressure or temperature applied during imprinting.…”
Section: The Cavity-fill Processmentioning
confidence: 95%
“…In the case of the rightmost geometry, the polymer is squeezed beneath the mold, and this squeezed flow significantly limits the time required to fill this cavity. [92] The ability to displace a viscous polymer and fill cavities can be demonstrated in another example, in which NIL is used to form an optical waveguide directly from a very thin polymer layer. The device is a polymer-based optical microring resonator, [68] which can find applications in optical communication, label-free biosensing, [93] and high-frequency ultrasound detection.…”
Section: The Cavity-fill Processmentioning
confidence: 98%
“…Feature-scale simulation using continuum material models There have been several attempts to describe TNIL through the finite-element modeling of very simple geometries [18][19][20][21][22]. The embossed material layer has variously been described as a Newtonian liquid [18][19][20], [23], as a shear-thinning liquid [18], and with linear viscoelastic [21], [24] models. Surface tension effects have generally been regarded as negligible in the simulation of TNIL, where the polymer's viscosity during imprinting is usually at least 10 3 Pa.s and bulk forces are considered to dominate over surface forces.…”
Section: Simulation Approachesmentioning
confidence: 99%